Epistemic Responsibility in Political Discourse (on Materials of D. Trump’s Press Conference) - A. I. Chepurnaya (Научный диалог, 2017)
The results of research on the linguistic marking of epistemic responsibility of the subject of political discourse are presented. The material is the speech of the elected President of the United States D. Trump at a press conference on 11 January 2017. The study was conducted using the methods of linguistic description, discourse, quantitative and content analysis. Two types of use of evidence-epistemic markers in the speech of a politician are identified. The first type of markers is focused on epistemic responsible representation of information, that is actually the marking of epistemic responsibility. It is shown that in this case there is a decrease or increase in epistemic responsibility through the use of indicators of problematic or categorical reliability, primarily predicates of views in the main part of the complex sentence and epistemic adverbs with the semantics of possibility / probability or confidence. The second type of markers involves manipulating the mind of the recipient. It is shown that in this case the markers of indirect evidentiality based on external unspecified source of information are used for the purpose of blurring of the guarantor or confirming the accuracy of statements, giving the information as included in the general fund of knowledge of the recipient and addressee, as well as presenting opinions as factual statements.